Digital native students’ perceived competence on digital literacy: A study of digital native students at a private Islamic junior high boarding school - Nurul Alfia; Sumardi Sumardi; Diah Kristina (Universitas Lampung, 2020)
The development of digital technology affects human life, especially for those born in the digital era (digital native). This can be seen from several aspects such as aspects of social life and learning styles that are different from previous generations. The digital native generation mostly spends most of their time on the internet, this naturally develops digital competencies. As a result, they are freely accessing information, whether related to academic interests or not, establish online relationships, play video games, and other exploration activities. Different results may be found in Private Islamic Junior High Boarding schools, where students are restricted from using gadgets. For this reason, the focus of this research is to find out the digital native students’ perceived digital literacy competencies in a Private Islamic Junior High Boarding school used the case study. This research took 54 students of the Private Islamic Junior High Boarding schools in Surakarta with purposive sampling techniques. The results of this study revealed that students’ photo-visual literacy, reproduction literacy, branching literacy, information literacy, socio-emotional thinking literacy, and the real-time thinking literacy were categorized as intermediate. http://dx.doi.org/10.23960/aksara/v21i1.pp74-87